Thermophysical properties of 1-butyl-3-methylimidazolium octyl sulfate ionic liquid in aqueous and aqueous electrolyte solutions at different temperatures - Anuja Jain; Ankita S. Chandak; Sangesh P. Zodape (Journal of Ionic Liquids, 2022)
Understanding the molecular interaction of 1-butyl-3-methylimidazolium octyl sulfate i.e., [Bmim][OcOSO3] in water and in aqueous NaCl solution is important for fabricating the new process. As it is already known that ionic liquids along with inorganic salt NaCl have significant potential in the tribology of lubricants and salting-out media for the separation of nicotine. It is known that ionic liquids exhibit characteristic behavior at solid−liquid interfaces. Although it is believed that the structure of ionic liquids at the interface contributes to the tribological properties in the region of boundary-mixed lubrication, this contribution has not been clarified yet. Thus, we study the molecular interaction of the ionic liquid in aqueous and ionic liquid in aqueous NaCl solutions through the thermodynamic approach. We have measured density as an important parameter for 1-butyl-3-methylimidazolium octyl sulfate i.e., [Bmim][OcOSO3] in water and in aqueous NaCl solution within the concentration range of 0.04-0.12 mol/kg at different temperatures i.e. 293.15, 298.15, 303.15, 308.15, and 313.15 K and atmospheric pressure by using a densitometer (DSA5000M Anton Paar). The density (ρ) data were employed to measure some derived parameters such as apparent molar volume of solute (Vϕ), limiting apparent molar volume of solute (Vϕ0), thermal expansion coefficient (α), apparent molar expansivity of solute at finite concentration (Eϕ) and at infinite concentration (Eϕ0) and transfer volume (ΔtrVϕ0). Results have been discussed in terms of all the possible molecular interactions in systems.